OSOBY STARSZE GRUPĄ O PODWYŻSZONYM STOPNIU RYZYKA WIKTYMIZACJI - Redakcja (Wydział Prawa i Administracji UAM, 1999)
Despite of the fact that the elderly become more rarely victims of a crime than younger persons - the results of such a victimisation are for them decidedly worse, according to general opinion. This concerns not only physical and psychological harms, but also - the moral wrongs and, finally, clearly more limited possibilities of properly reacting to a situation. All of this is being accompanied with a high level of the fear of a crime. The fear increases with the ageing process and is mainly irrationally distorted by, among others, the mass-media. Important is also the fact that the elderly are fully aware of their particular situation and of high risk of victimisation. As a result it only makes the isolation deeper and a level of the threat raises.
THE ELDERLY AS A GROUP OF INCREASED DEGREE OF A VICTIMISATION RISK